Isaac N. Phillips, The Revised Ordinances of the City of Bloomington, A.D. 1876: Comprising the general ordinances, acts of incorporation, and other laws affecting the City of Bloomington (Bloomington, IL: Leader Steam Printing and Publishing House, 1876), 9. Chapter 2. Cemeteries, Section 1. §10. Shooting, Trespassing, etc.--Penalty - (:unkn) unknown (General Publisher, 1876)
Prohibited discharging any firearm, or hunting, or trespassing within the city cemetary or any other cemetary or burying ground within the city. Violators fined not less than ten nor more than one hundred dollars.
--
Keywords: DISCHARGE